Efektivitas Implementasi Kebijakan Publik dalam Mewujudkan Pelayanan Publik yang Responsif: Tinjauan Teoritis dan Empiris - Addawiyah Addawiyah; Lolita Febriani; Nurul Fadillah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the effectiveness of public policy implementation in realizing responsive public services with a literature review approach. The focus of the study is directed at conceptual understanding of the dimensions of policy effectiveness, the characteristics of responsive public services, the relationship between policy and service quality, and implementation challenges in the field. The method used is a descriptive qualitative method based on literature studies from various theoretical and empirical sources. The results of the study show that the effectiveness of implementation is highly correlated with the quality of public services, where factors such as resources, inter-agency coordination, and community involvement are the main keys to success. Bureaucratic reform strategies, capacity building of apparatus, and open and adaptive governance are needed to realize public services that truly answer the needs of the community.